COMPARISONAL ANALYSIS OF RECEIVABLE AND TRADE DEBT BUDGETING IN MSME FINANCIAL STATEMENTS - Catresia Caterindah; Dian Hakip Nurdiansyah (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2022)
In the era of the COVID-19 pandemic, this is a new challenge for MSME business actors in Indonesia. There are so many problems that occur such as reducing employees, a lot of unemployment, people who are starting to get used to living with new patterns of habits and activities such as staying at home, working from home, and studying at home. MSME actors must think hard in maintaining and making new innovations in strengthening their business for their daily needs. This study aims to analyze the financial performance or performance of Hasan STIM MSMEs on April 1, 2020 & June 1, 2020. In April 2020 there was the highest increase in income. high in 2020 because this month coincides with the Eid homecoming season and school holidays. Many families, tourism buses, and even other four-wheeled land transportation use STIM services on Hasan STIM. In the financial statements of SMEs Hasan STIM does not use accounting records but through simple cash book records. Here the author analyzes as well as helps calculate how much total assets, total liabilities, total equity, total income and total net income. In this case the condition of Hasan STIM's financial statements on accounts payable and accounts receivable has experienced ups and downs, especially the impacts caused by previous needs not purchased must be purchased and soaring equipment prices caused unstable financial conditions, especially in payables and accounts receivable. The analysis used in this study is a comparison of the budget on April 1, 2020 with June 1, 2020, which shows that the financial condition of the MSME business at Hasan STIM is quite good and has increased sales in April and decreased in June. Hasan STIM's financial report shows less debt than assets and profits.